The impact of work concerns on teaching effectiveness: A structural equation modeling and multiple regression analysis in Chinese private universities - Mingyu Liang; Mohd Khairuddin Abdullah @Jerry Abdullah; Qun Wang (Frontiers Media S.A., 2025)
It is crucial to understand how young teachers cope with work concerns for improving teaching quality in the Chinese private higher education institutions. This study investigates the relationship between different stages of such concerns and teacher effectiveness among young lecturers in private universities. These lecturers often face workload pressure and a lack of career support, which may influence their professional development and teacher effectiveness. This research involved 416 full-time lecturers under 40 from four private universities located in Shandong Province. The sample was selected through a multi-stage sampling method: private universities were stratified into four categories, one university from each category was purposively selected, and participants were randomly sampled. Data were collected using a structured questionnaire based on the Stages of Concern and the School Teacher Effectiveness Questionnaire. Pearson correlation, multiple regression, and structural equation modeling were conducted for analysis. Results show that task concerns and impact concerns significantly influenced teacher effectiveness across three dimensions: instructional planning and strategies, assessment, and learning environment. In contrast, self-concerns showed weaker influence. These findings suggest that work concerns reflect not only stress but also deeper professional motivation, pointing to the need for more targeted support strategies to improve teacher effectiveness and career growth.